The Relationship Between Education Inequality, Poverty, and Economic Growth - Yasir, Hamdan; Susetyo, Didik; Bashir, Abdul (SAFE-Network, 2024)
This study aims to establish the relationship between education inequality, poverty, and economic growth in the 10 Provinces of Sumatra Island 2004-2022. The data used is secondary data sourced from the Badan Pusat Statistik (BPS). The analytical approach employed encompasses the Panel Vector Error Correction Model (PVECM) along with Granger Causality. The findings indicate the presence of both short-term and long-term associations between education inequality and economic growth concerning poverty levels in the 10 Provinces of Sumatra Island. Furthermore, a bidirectional connection is observed between education inequality and economic growth within the 10 Provinces of Sumatera Island. Conversely, a unidirectional linkage is identified between economic growth and poverty in the 10 Province of Sumatera Island. It is anticipated that governmental policies will aim to enhance educational aspects and promote public consciousness regarding education to bolster developmental investments across various regional autonomies at both the Regency/City and Province tiers in Indonesia.